1997
DOI: 10.1073/pnas.94.21.11445
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations for the Met tyrosine kinase receptor in human cancer

Abstract: Recently, mutations in the Met tyrosine kinase receptor have been identified in both hereditary and sporadic forms of papillary renal carcinoma. We have introduced the corresponding mutations into the met cDNA and examined the effect of each mutation in biochemical and biological assays. We find that the Met mutants exhibit increased levels of tyrosine phosphorylation and enhanced kinase activity toward an exogenous substrate when compared with wild-type Met. Moreover, NIH 3T3 cells expressing mutant Met molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
334
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 407 publications
(342 citation statements)
references
References 47 publications
5
334
0
3
Order By: Relevance
“…Substitution of these residues is responsible for the oncogenic conversion of Kit and Ret receptors (Kitayama et al, 1995;Santoro et al, 1995), and causes subversion of substrate speci®city (Songyang and Cantley, 1995;Santoro et al, 1995, Piao andBernstein, 1996). Recently these activating mutations have been found also in Met, in sporadic and hereditary papillary renal carcinomas Je ers et al, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…Substitution of these residues is responsible for the oncogenic conversion of Kit and Ret receptors (Kitayama et al, 1995;Santoro et al, 1995), and causes subversion of substrate speci®city (Songyang and Cantley, 1995;Santoro et al, 1995, Piao andBernstein, 1996). Recently these activating mutations have been found also in Met, in sporadic and hereditary papillary renal carcinomas Je ers et al, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…The missense mutation in exon 17 (Case 3) is one of the most commonly mutated regions of the tyrosine kinase domain of MET. Mutation studies on known mutations identified in papillary renal carcinoma exhibited increased levels of tyrosine phosphorylation and enhanced kinase activity in response to exogenous ligands when compared with wild-type MET (29). Moreover, NIH 3T3 cells expressing mutant MET molecules formed foci in vitro and were tumorigenic in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that mutationally activated Met mediates the transformation and tumorigenicity of NIH3T3 cells (Je ers et al, 1997a). However, for the present investigation we were concerned that the endogenous production of both Met and HGF/SF by these cells could interfere with our proposed experiments.…”
mentioning
confidence: 95%
“…Finally, Met can be oncogenically activated via a number of speci®c point mutations introduced into its kinase domain. Mutations originally identi®ed in human papillary renal carcinomas were found to generate Met molecules possessing constitutive kinase activity and transforming ability (Je ers et al, 1997a;Schmidt et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation